Prenatal and Postnatal Diagnosis and Genetic Background of Corpus Callosum Malformations and Neonatal Follow-Up - Virág Bartek; István Szabó; Ágnes Harmath; Gábor Rudas; Tidhar Steiner; Attila Fintha; Nándor Ács; Artúr Beke (MDPI AG, 2024)
Introduction: The corpus callosum is one of the five main cerebral commissures. It is key to combining sensory and motor functions. Its structure can be pathological (dysgenesis) or completely absent (agenesis). The corpus callosum dys- or agenesis is a rare disease (1:4000 live births), but it can have serious mental effects. Methods: In our study, we processed the data of 64 pregnant women. They attended a prenatal diagnostic center and genetic counseling from 2005 to 2019 at the Department of Obstetrics and Gynecology at Semmelweis University. Results: The pregnancies had the following outcomes: 52 ended in delivery, 1 in spontaneous abortion, and 11 in termination of pregnancy (TOP) cases (n = 64). The average time of detection with imaging tests was 25.24 gestational weeks. In 16 cases, prenatal magnetic resonance imaging (MRI) was performed. If the abnormality was detected before the 20th week, a genetic test was performed on an amniotic fluid sample obtained from a genetic amniocentesis. Karyotyping and cytogenetic tests were performed in 15 of the investigated cases. Karyotyping gave normal results in three cases (46,XX or XY). In one of these cases, postnatally chromosomal microarray (CMA) was later performed, which confirmed Aicardi syndrome (3q21.3-21.1 microdeletion). In one case, postnatally, the test found Wiedemann-Rautenstrauch syndrome. In other cases, it found X ring, Di George syndrome, 46,XY,del(13q)(q13q22) and 46,XX,del(5p)(p13) (Cri-du-chat syndrome). Edwards syndrome was diagnosed in six cases, and Patau syndrome in one case. Conclusions: We found that corpus callosum abnormalities are often linked to chromosomal problems. We recommend that a cytogenetic test be performed in all cases to rule out inherited diseases. Also, the long-term outcome does not just depend on the disease's severity and the associated other conditions, and hence proper follow-up and early development are also key. For this reason, close teamwork between neonatology, developmental neurology, and pediatric surgery is vital.